A bimetallic, bidisperse stabilizer catalyst and its preparation method and application

Through the catalyst preparation method of modified alumina support and bimetal and bidispersing stabilizers, the problems of carrier shrinkage and channel blockage of precious metal catalysts during the heat treatment process are solved, the catalytic performance and precious metal utilization rate are improved, and the preparation cost is reduced.

CN119746849APending Publication Date: 2025-04-04SHANGHAI LVQIANG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411923241.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing precious metal catalysts are prone to carrier shrinkage and channel blockage during heat treatment, resulting in a decrease in catalytic performance and a decrease in precious metal utilization.

Method used

Modified alumina is used as a support, and a catalyst of bimetallic and bidispersing stabilizer is prepared by adding silicon support material and dispersant, combined with mechanical stirring and equal volume impregnation methods, thereby improving the dispersion and binding force of precious metals on the support.

Benefits of technology

It effectively solves the problems of support heat treatment shrinkage and channel blockage, improves the utilization rate of precious metals and the catalytic performance of catalysts, and reduces the cost of catalyst preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208566820000061
    Figure BDA0005208566820000061
Patent Text Reader

Abstract

The present invention relates to a catalyst of bimetallic and double dispersion stabilizer and its preparation method and application, wherein the active component in the catalyst adopts the bimetallic of precious metal and transition metal, and the dispersion stabilizer in the auxiliary agent adopts the double dispersion stabilizer of organic solvent and organic acid; an alumina precursor, a supporting material and a dispersant are mixed and dried to obtain modified alumina, the modified alumina and transition metal precursor are mixed and molded, roasted to obtain a modified alumina-metal composite carrier, the dispersion stabilizer and the precious metal precursor are mixed, impregnated on the modified alumina-metal composite carrier, roasted, and a bimetallic and double dispersion stabilizer catalyst is obtained. Compared with the prior art, the present invention solves the problem of catalyst carrier heat treatment shrinkage, improves the problem of catalyst pore blockage, improves the dispersion efficiency of precious metals on the carrier, reduces the aggregation and loss of precious metals during heating, improves the utilization rate of precious metals, reduces the cost of catalyst preparation, and improves the catalytic performance of catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and relates to a bimetallic, bidisperse stabilizer catalyst, a preparation method and application thereof. Background Art

[0002] Precious metal catalysts are widely used in the field of industrial catalysis due to their excellent catalytic performance and outstanding stability. For example, they are used to varying degrees in catalytic combustion reactions of reducing gases such as methane, carbon monoxide, hydrogen, and volatile organic compounds (VOCs).

[0003] At present, the main catalysts for catalytic methane combustion can be mainly divided into precious metal palladium, platinum and other catalysts and non-precious metal catalysts according to element classification. Patents CN103372447A and CN102500393A disclose non-precious metal catalysts, such as perovskite-type and hexaaluminate-type catalysts, which have stable structures and low prices, but have high ignition temperatures, poor activity, and are greatly affected by water-containing atmospheres; the precious metal catalysts disclosed in patent CN102500393A have the advantages of high activity, long life, and good water resistance; patent CN109569678A discloses a method for preparing a carbon monoxide catalytic combustion catalyst, which has good sintering resistance and stability, can remove carbon monoxide at room temperature, and can operate under high temperature conditions. These indicate that precious metal catalysts have become the mainstream research direction of catalytic combustion.

[0004] Most of the current precious metal catalysts are supported catalysts. Precious metals can only be loaded onto the carrier by relying on the physical adsorption properties of the carrier, and the precious metals need to be fixed on the carrier by heat treatment. In this case, some of the loaded precious metals enter the pores of the carrier. Due to the crystallization and shrinkage deformation of alumina during the heat treatment, some of the pores are easily blocked, and the precious metals loaded and blocked in the pores cannot play a role. Therefore, there is a problem that the actual amount of precious metal added is much higher than the theoretical amount, and the catalytic performance of the catalyst is reduced because the pores are not smooth. At the same time, since the precious metal and the carrier are only combined by simple physical adsorption, the force is small, and precious metals are prone to aggregation and loss during heat treatment and high-temperature use, resulting in a significant decrease in the utilization rate of the precious metals, and the catalytic performance of the catalyst will also decrease.

[0005] Patent CN117753435A discloses a single-atom alloy catalyst, a preparation method thereof, and an application in selective hydrogenation conversion technology. The catalyst is represented by M1-X1-Y / SA. The structural characteristics of the catalyst are: M1 and X1 form an atomically dispersed dual-center single-atom alloy with Y, and the M1-X1-Y dual-center single-atom alloy is stably and evenly distributed on the carrier; the preparation method is to adopt a modified sol fixation-impregnation coupling strategy, control the particle size of the active metal nucleation process by regulating the supersaturation of the sol, and interact with the auxiliary metal to form atomically dispersed and coordinated unsaturated X1-Y bimetallic particles, and use the acid-treated carrier surface sites as anchoring centers to make the X1-Y bimetallic particles highly dispersed on the carrier surface; further, the active precious metal M1 is loaded on the coordinated unsaturated sites of the X1-Y bimetallic particles, thereby constructing a stable and synergistically enhanced M1-X1-Y dual-center single-atom alloy catalyst. Since the carrier of this patent is mixed with the metal sol during the impregnation process, this will inevitably cause difficulties in metal mass transfer during the impregnation process, resulting in uneven distribution of the metal on the carrier, which is inconsistent with the statement in the patent that the X1-Y bimetallic particles are evenly dispersed on the carrier surface.

[0006] Patent CN109306136A discloses a flame-retardant polyvinyl chloride plastic particle and a preparation method thereof. The preparation process is as follows: a carbon precursor material is dissolved in N,N-dimethylformamide, and white carbon black and white carbon black ethylene glycol dispersion are added in sequence; the resulting mixed solution is transferred to a Petri dish, placed in an oven for drying, the resulting powder is calcined, the silica is removed, and then the powder is washed several times with deionized water and dried to obtain a carrier, which is recorded as pc-C; a Cu precursor solution is prepared, and the solution is slowly dripped onto the carrier according to an equal volume impregnation method, and after standing, the solution is dried to obtain Cu / pc-C; a noble metal precursor solution is prepared, and the solution is slowly dripped onto the carrier according to an equal volume impregnation method, and after standing, the solution is dried to obtain AuCu / pc-C or PtCu / pc-C or PdCu / pc-C. Although this patent has processed the catalyst carrier part, it has not carried out targeted control of the impregnation conditions of the main active component metal of the catalyst. On the one hand, it has not improved the dispersion of the metal on the carrier and firmly fixed it on the carrier. On the other hand, the treatment of the carrier has not improved the shrinkage and pore blockage problems. Summary of the invention

[0007] The purpose of the present invention is to provide a bimetallic, bidisperse stabilizer catalyst and its preparation method and application in order to overcome at least one defect of the above-mentioned prior art. The present invention specifically solves the problem of catalyst carrier shrinkage during heat treatment and improves the problem of catalyst pore blockage. At the same time, it improves the dispersion efficiency of precious metals on the carrier while reducing the aggregation and loss of precious metals during heating, ultimately achieving the purpose of improving the utilization rate of precious metals, reducing the cost of catalyst preparation, and improving the catalytic performance of the catalyst.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] One of the technical solutions of the present invention is to provide a bimetallic, bidisperse stabilizer catalyst, the catalyst comprising a carrier, an active component and an auxiliary agent, the carrier is modified alumina, the active component is a bimetallic of a noble metal and a transition metal, the auxiliary agent is a supporting material, a dispersant and a dispersion stabilizer, and the dispersion stabilizer is a bidisperse stabilizer of an organic solvent and an organic acid;

[0010] The aluminum oxide precursor, the supporting material and the dispersant are mixed and dried to obtain modified aluminum oxide.

[0011] The modified alumina and transition metal precursor are mixed, molded, and calcined to obtain a modified alumina-metal composite carrier.

[0012] The dispersion stabilizer and the noble metal precursor are mixed, impregnated on a modified alumina-metal composite carrier, and calcined to obtain a bimetallic, bidispersion stabilizer catalyst.

[0013] Furthermore, the alumina precursor is selected from one or more of pseudo-boehmite, aluminum sol, and aluminum hydroxide, the supporting material is selected from one or more of white carbon black and macroporous silica gel, and the dispersant is selected from one or more of sodium polyacrylate and polyethylene glycol.

[0014] Furthermore, the support material has a developed pore structure, and the specific surface area of ​​the support material is greater than 400m 2 / g, pore volume greater than 2.5cm 3 / g, pore size larger than

[0015] As a preferred technical solution, the molecular weight of the polyethylene glycol is 200 to 20,000.

[0016] Furthermore, the transition metal precursor is a transition metal oxide, and the transition metal is selected from one of titanium (Ti), cerium (Ce), and zirconium (Zr).

[0017] The noble metal precursor is selected from one or more of noble metal hydrochlorides and noble metal nitrates, and the noble metal is selected from one of palladium (Pd) and platinum (Pt).

[0018] The organic solvent is selected from one of ethanol, methanol, isopropanol, acetonitrile and tetrahydrofuran, and the organic acid is selected from one of lactic acid, acetic acid, citric acid and glycolic acid.

[0019] Furthermore, the amount of the support material added is calculated by the mass of silicon dioxide (SiO2), the amount of the alumina precursor added is calculated by the mass of alumina (Al2O3), and the mass fraction of the support material compared to the alumina precursor is 1-10%.

[0020] The mass fraction of the dispersant compared to the alumina precursor is 1 to 10%.

[0021] The amount of the transition metal precursor added is calculated based on the mass of the oxide, and the mass fraction of the transition metal precursor compared to the aluminum oxide precursor is 5 to 20%.

[0022] The amount of the noble metal precursor added is calculated based on the mass of the oxide, and the mass fraction of the noble metal precursor compared to the modified alumina-metal composite carrier is 0.1-1%.

[0023] The mass fraction of the organic solvent relative to the modified alumina-metal composite carrier is 10-50%, and the mass fraction of the organic acid relative to the modified alumina-metal composite carrier is 5-20%.

[0024] One of the technical solutions of the present invention is to provide a method for preparing the bimetallic, bidisperse stabilizer catalyst, the method comprising the following steps:

[0025] S1, dispersing an alumina precursor in water, adding a supporting material and a dispersant, and continuing to mix, fine grinding and spray drying to obtain modified alumina;

[0026] S2, mixing the modified alumina and the transition metal precursor, drying and calcining to obtain a modified alumina-metal composite carrier;

[0027] S3. Mix the dispersion stabilizer and the noble metal precursor to obtain an impregnation solution, impregnate the impregnation solution onto the modified alumina-metal composite carrier, dry and calcine to obtain a bimetallic, bidispersion stabilizer catalyst.

[0028] Furthermore, the mixing temperature in step S1 is 10 to 60° C. and the mixing time is 1 to 4 hours.

[0029] The inlet air temperature for spray drying is 250-400°C.

[0030] As a preferred technical range, the rotation speed of fine grinding in step S1 is 1000-3000 r / min, and the time is 0.5-2 h.

[0031] Furthermore, the temperature of the mixed molding in step S2 is 10 to 60°C.

[0032] The drying temperature is 80-150°C and the drying time is 2-6 hours.

[0033] The calcination temperature is 500-700°C and the calcination time is 2-6 hours.

[0034] Furthermore, the mixing temperature in step S3 is 40 to 80° C. and the mixing time is 0.5 to 2 h.

[0035] The impregnation adopts equal volume impregnation, the impregnation temperature is 10-60℃, and the time is 0.5-2h.

[0036] The drying temperature is 80-150°C and the drying time is 2-6 hours.

[0037] The calcination temperature is 400-600°C and the calcination time is 2-6 hours.

[0038] As a preferred technical solution, the catalyst is calcined in step S3, then cooled, and reduced in a reducing atmosphere.

[0039] As a preferred technical solution, the reducing gas in the reducing atmosphere is hydrogen, and the reducing gas content is 1-20%.

[0040] As a preferred technical solution, the reduction temperature is 150-300° C. and the time is 0.5-2 h.

[0041] One of the technical solutions of the present invention is to provide an application of the bimetallic, bidisperse stabilizer catalyst, wherein the catalyst is applied to the catalytic oxidation of reducing gases or volatile organic compounds (VOCs).

[0042] As a preferred technical solution, the reducing gas is selected from one or more of methane, carbon monoxide, and hydrogen, and the reducing gas content is 0.5-10%.

[0043] As a preferred technical solution, the temperature of the catalytic oxidation is 25-600°C, and the volume space velocity is 10000-30000h -1 .

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The present invention improves the shrinkage problem of the carrier under heat treatment by adding a certain amount of silicon support material during the carrier preparation process. Adding a small amount of silicon support material can increase the crystallization temperature of the alumina carrier. At the same time, the silicon support material with a suitable shape can support the pore structure, thereby improving the catalyst pore blockage problem by improving the shrinkage problem of the carrier;

[0046] (2) Excessive silicon support material concentrated in some areas is prone to pore blockage. The present invention can more evenly disperse a small amount of silicon support material into the alumina carrier by adding a dispersant and fine grinding, thereby providing better support for the carrier. After forming, a porous modified alumina-metal composite carrier with large pore size and high specific surface area can be prepared by heat treatment;

[0047] (3) Ordinary noble metals with high content can be evenly mixed with alumina carrier by mechanical stirring. However, noble metals are usually expensive. In order to control the cost of catalyst preparation, the amount of noble metal added needs to be controlled. In the present invention, a small amount of noble metal is dissolved in a dispersant and then the noble metal dissolved in the dispersant is stably impregnated into a porous modified alumina-metal composite carrier by an equal volume impregnation method. The organic acid in the dispersant is stably combined with the noble metal ions. The organic solvent can effectively disperse the combination of the organic acid and the noble metal ions, and stably disperse the organic acid groups containing the noble metal ions onto the carrier. The dispersant can prevent the noble metals from aggregating, and improve the dispersion degree and dispersion efficiency of the noble metals on the carrier. At the same time, the noble metals that have been impregnated on the carrier can be stably fixed on the carrier, thereby improving the binding force between the noble metals and the carrier, reducing the loss of noble metals during heat treatment, and ultimately improving the utilization rate of the noble metals, reducing the cost of catalyst preparation, and improving the catalytic performance of the catalyst. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0049] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.

[0050] Modified alumina preparation:

[0051] Weigh 200 g of pseudo-boehmite, 2.6 g of macroporous silica gel, 400 g of pure water, and 6 g of sodium polyacrylate. Pseudo-boehmite is used as alumina precursor, and macroporous silica gel is used as support material S. The specific surface area of ​​macroporous silica gel is 450 m 2 / g, pore volume is 2.6cm 3 / g, pore size The amount of macroporous silica added is 2.5 g in terms of the mass of silicon dioxide (SiO2), the amount of pseudo-boehmite added is 130 g in terms of the mass of alumina (Al2O3), the ratio of macroporous silica to pseudo-boehmite, SiO2:Al2O3=1.9%, sodium polyacrylate is used as a dispersant, N:Al2O3=4.6%, pseudo-boehmite is dispersed in pure water, stirred evenly at 25°C for 1 hour, macroporous silica gel and sodium polyacrylate are added and stirred evenly for 1 hour, and after being mixed evenly, the mixture is put into a horizontal sand mill and heated at 2000 The modified alumina was finely ground at 400 r / min for 1 h, spray dried at an inlet air temperature of 350°C to obtain the modified alumina, calcined at 550°C, and the physical adsorption properties were measured by a physical adsorption instrument. 2.6 g of macroporous silica gel was used as the Al2O3 carrier of the supporting material S as A-1, 2.6 g of polyethylene glycol 20000 was used as the Al2O3 carrier of the supporting material S as A-2, 2.6 g of sesbania powder was used as the Al2O3 carrier of the supporting material S as A-3, and 2.6 g of starch was used as the Al2O3 carrier of the supporting material S as A-4.

[0052] The comparison of physical adsorption test results is shown in Table 1.

[0053] Table 1 Physical adsorption properties of A-1, A-2, A-3 and A-4

[0054]

[0055] As shown in Table 1, the pore structure of the carrier with silicon support material is significantly better than that of the carrier with other support materials. Although the specific surface area is not much different, the pore volume and pore size are several times different. Catalyst carriers with large pore volume and pore size are not only conducive to the entry of metal ions, but also conducive to the entry of reactants and the smooth diffusion of products, reducing the occurrence of side reactions and improving the selectivity of products.

[0056] Preparation of modified alumina-metal composite carrier:

[0057] Weigh 13g of titanium dioxide (TiO2), TiO2 as the transition metal precursor M, M:Al2O3=10%, mix the modified alumina A-1 and TiO2 at 25°C, dry at 120°C for 4h, and calcine at 600°C for 4h to obtain a modified alumina-metal composite carrier, 13g TiO2 as the Ti-Al2O3 carrier of the transition metal precursor M is recorded as AZ-1, 13g cerium dioxide (CeO2) as the Ce-Al2O3 carrier of the transition metal precursor M is recorded as AZ-2, and 13g zirconium dioxide (ZrO2) as the Zr-Al2O3 carrier of the transition metal precursor M is recorded as AZ-3.

[0058] Embodiment 1:

[0059] A bimetallic, bidisperse stabilizer catalyst and a preparation method thereof, the specific steps are as follows:

[0060] Weigh 9.4 g of tetrahydrofuran, 2.6 g of glycolic acid, and 0.05 g of palladium chloride (PdCl2), with PdCl2 as the noble metal precursor G, the amount of PdCl2 added being 0.034 g based on the mass of the oxide, G:AZ-1=0.17%, tetrahydrofuran as the organic solvent R in the dispersion stabilizer, R:AZ-1=47%, glycolic acid as the organic acid C in the dispersion stabilizer, C:AZ-1=13%, and fully mix and dissolve tetrahydrofuran, glycolic acid and PdCl2 at 60°C for 1 h to obtain a clear solution , obtain the impregnation solution; then weigh 20g AZ-1 carrier, use the equal volume impregnation method to impregnate the impregnation solution on the AZ-1 carrier at 25°C for 1h, dry at 120°C for 4h, and calcine at 500°C for 4h. After cooling, use 10% hydrogen / 90% argon (10% H2 / 90% Ar) to reduce at 250°C for 1h to obtain a bimetallic, bidisperse stabilizer catalyst, 9.4g tetrahydrofuran as the organic solvent R in the dispersion stabilizer, 2.6g hydroxyacetic acid as the organic acid C in the dispersion stabilizer, and 0.05g PdCl2 as the precious metal precursor G. The Pd / Ti-Al2O3 catalyst is recorded as S-1.

[0061] Embodiment 2:

[0062] A bimetallic, bidisperse stabilizer catalyst and a preparation method thereof are basically the same as Example 1, except that 9.4 g of tetrahydrofuran, 2.6 g of hydroxyacetic acid, and 0.2 g of PdCl2 are weighed, PdCl2 is used as the precious metal precursor G, the amount of PdCl2 added is 0.138 g based on the mass of the oxide, G:AZ-1=0.69%, 9.4 g of tetrahydrofuran is used as the organic solvent R in the dispersion stabilizer, 2.6 g of hydroxyacetic acid is used as the organic acid C in the dispersion stabilizer, and 0.2 g of PdCl2 is used as the Pd / Ti-Al2O3 catalyst of the precious metal precursor G is recorded as S-2.

[0063] Embodiment 3:

[0064] A bimetallic, bidisperse stabilizer catalyst and a preparation method thereof are basically the same as those in Example 1, except that the impregnation liquid is impregnated into an AZ-2 carrier at 25°C for 1 hour, 9.4 g of acetonitrile is used as the organic solvent R in the dispersing stabilizer, 2.6 g of lactic acid is used as the organic acid C in the dispersing stabilizer, and 0.05 g of PdCl2 is used as the precious metal precursor G. The Pd / Ce-Al2O3 catalyst is recorded as S-3.

[0065] Embodiment 4:

[0066] A bimetallic, bidisperse stabilizer catalyst and a preparation method thereof are basically the same as those in Example 1, except that the impregnation liquid is impregnated into an AZ-2 carrier at 25°C for 1 hour, 9.4 g of acetonitrile is used as the organic solvent R in the dispersing stabilizer, 2.6 g of lactic acid is used as the organic acid C in the dispersing stabilizer, and 0.2 g of PdCl2 is used as the precious metal precursor G. The Pd / Ce-Al2O3 catalyst is recorded as S-4.

[0067] Embodiment 5:

[0068] A bimetallic, bidisperse stabilizer catalyst and a preparation method thereof are basically the same as those in Example 1, except that the impregnation liquid is impregnated into an AZ-3 carrier at 25°C for 1 hour, 9.4 g of acetonitrile is used as the organic solvent R in the dispersing stabilizer, 2.6 g of lactic acid is used as the organic acid C in the dispersing stabilizer, and 0.05 g of PdCl2 is used as the precious metal precursor G. The Pd / Zr-Al2O3 catalyst is recorded as S-5.

[0069] Embodiment 6:

[0070] A bimetallic, bidisperse stabilizer catalyst and a preparation method thereof are basically the same as those in Example 1, except that the impregnation liquid is impregnated into an AZ-3 carrier at 25°C for 1 hour, 9.4 g of acetonitrile is used as the organic solvent R in the dispersing stabilizer, 2.6 g of lactic acid is used as the organic acid C in the dispersing stabilizer, and 0.2 g of PdCl2 is used as the precious metal precursor G. The Pd / Zr-Al2O3 catalyst is recorded as S-6.

[0071] Comparative Example 1:

[0072] A catalyst and a preparation method thereof are basically the same as those in Example 1, except that the impregnation liquid is impregnated into a common alumina carrier (A-4) at 25°C for 1 hour, 9.4 g of acetonitrile is used as the organic solvent R in the dispersion stabilizer, 2.6 g of hydroxyacetic acid is used as the organic acid C in the dispersion stabilizer, and 0.2 g of PdCl2 is used as the precious metal precursor G. The Pd / Al2O3 catalyst is recorded as S-7.

[0073] Comparative Example 2:

[0074] A catalyst and a preparation method thereof are basically the same as those in Example 1, except that the impregnation liquid is impregnated into the AZ-3 carrier at 25°C for 1 hour, 12 g of 3% hydrochloric acid solution is used as a dispersion stabilizer, and 0.2 g of PdCl2 is used as the Pd / Zr-Al2O3 catalyst of the precious metal precursor G is recorded as S-8.

[0075] The dispersion of palladium (Pd) was measured on the above catalyst, and the specific steps are as follows:

[0076] Weigh 20 mg of catalyst, first pre-treat the catalyst, purge with helium (He), heat from 60°C to 200°C at a heating rate of 20°C / min, keep warm for 40 minutes, and cool down to 60°C; then, in a 10% H2 / 90% Ar atmosphere, heat from 60°C to 300°C at a heating rate of 5°C / min, keep warm for 1 hour, and cool down to 50°C; then, introduce 5% H2 / Ar pulses, and when the detected H2 peak height does not change, the adsorption is completed;

[0077] The relationship curve between H2 concentration and temperature was recorded online during the experiment;

[0078] The Pd dispersion was calculated by the software of the Micromeritics Auto Chem 2910 instrument and is shown in Table 2.

[0079] The above catalyst was subjected to catalytic oxidation determination, and the specific steps are as follows:

[0080] The catalyst was crushed into 20-40 meshes, 1 mL was taken, and the catalytic activity of the catalyst was evaluated using a fixed bed;

[0081] The reaction temperature is 410°C and the volume space velocity is 20000h -1 , the raw material is 1% methane / 99% argon (1% CH4 / 99% Ar).

[0082] The conversion efficiency of the catalyst to CH4 is shown in Table 2.

[0083] Table 2 Physical adsorption properties of the embodiments and comparative examples and their supporting materials

[0084] Case Sample name Pd dispersion (%) <![CDATA[CH4 conversion rate (%)]]> Example 1 S-1 46.1 75.9 Example 2 S-2 53.2 89.8 Example 3 S-3 43.5 73.3 Example 4 S-4 52.1 83.6 Example 5 S-5 48.7 82.3 Example 6 S-6 56.8 91.5 Comparative Example 1 S-7 43.1 64.6 Comparative Example 2 S-8 5.6 21.2

[0085] As shown in Table 2, in Comparative Example 2, hydrochloric acid is used as a dispersant, the Pd dispersion is only 5.6%, and the CH4 conversion rate in the catalytic reaction is only 21.2%. Compared with Comparative Example 2, the embodiments all use a dual-dispersion stabilizer of an organic solvent and an organic acid, and the Pd dispersion is generally close to 10 times that of Comparative Example 2, and the CH4 conversion rate in the catalytic reaction is generally close to 4 times that of Comparative Example 2, which highlights the great superiority of the dual-dispersion stabilizer of an organic solvent and an organic acid;

[0086] In Comparative Example 1, ordinary alumina without special treatment is used as the carrier. Compared with Comparative Example 1, the catalyst carrier is treated specifically in the embodiments, and the CH4 conversion rate in the catalytic reaction also has a more obvious advantage;

[0087] In summary, the performance of the carrier and the selection of impregnation conditions play a decisive role in the catalytic performance of the catalyst. The Pd / Zr-Al2O3 catalyst prepared with modified alumina-Zr metal composite as the carrier and acetonitrile and lactic acid as precious metal dispersion stabilizers has the best dispersion effect on Pd and catalytic oxidation of CH4.

[0088] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A bimetallic, bidisperse stabilizer catalyst, characterized in that: The catalyst comprises a carrier, an active component and an auxiliary agent, wherein the carrier is modified alumina, the active component is a bimetal of a noble metal and a transition metal, the auxiliary agent is a supporting material, a dispersant and a dispersion stabilizer, and the dispersion stabilizer is a dual dispersion stabilizer of an organic solvent and an organic acid; The aluminum oxide precursor, the supporting material and the dispersant are mixed and dried to obtain modified aluminum oxide. The modified alumina and transition metal precursor are mixed, molded, and calcined to obtain a modified alumina-metal composite carrier. The dispersion stabilizer and the noble metal precursor are mixed, impregnated on a modified alumina-metal composite carrier, and calcined to obtain a bimetallic, bidispersion stabilizer catalyst.

2. A bimetallic, bidisperse stabilizer catalyst according to claim 1, characterized in that: The alumina precursor is selected from one or more of pseudo-boehmite, aluminum sol, and aluminum hydroxide; the supporting material is selected from one or more of white carbon black and macroporous silica gel; and the dispersant is selected from one or more of sodium polyacrylate and polyethylene glycol.

3. A bimetallic, bidisperse stabilizer catalyst according to claim 1, characterized in that: The specific surface area of ​​the support material is greater than 400m 2 / g, pore volume greater than 2.5cm 3 / g, pore size larger than 4. A bimetallic, bidisperse stabilizer catalyst according to claim 1, characterized in that: The transition metal precursor is one or more transition metal oxides, and the transition metal is selected from one of titanium, cerium and zirconium. The noble metal precursor is selected from one or more of noble metal hydrochlorides and noble metal nitrates, and the noble metal is selected from one of palladium and platinum. The organic solvent is selected from one of ethanol, methanol, isopropanol, acetonitrile and tetrahydrofuran, and the organic acid is selected from one of lactic acid, acetic acid, citric acid and glycolic acid.

5. A bimetallic, bidisperse stabilizer catalyst according to claim 1, characterized in that: The amount of the support material added is calculated based on the mass of silicon dioxide, the amount of the alumina precursor added is calculated based on the mass of alumina, and the mass fraction of the support material compared to the alumina precursor is 1-10%. The mass fraction of the dispersant compared to the alumina precursor is 1 to 10%. The amount of the transition metal precursor added is calculated based on the mass of the oxide, and the mass fraction of the transition metal precursor compared to the aluminum oxide precursor is 5 to 20%. The amount of the noble metal precursor added is calculated based on the mass of the oxide, and the mass fraction of the noble metal precursor compared to the modified alumina-metal composite carrier is 0.1-1%. The mass fraction of the organic solvent relative to the modified alumina-metal composite carrier is 10-50%, and the mass fraction of the organic acid relative to the modified alumina-metal composite carrier is 5-20%.

6. A method for preparing a bimetallic, bidisperse stabilizer catalyst as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: S1, dispersing an alumina precursor in water, adding a supporting material and a dispersant, and continuing to mix, fine grinding, and spray drying to obtain modified alumina; S2, mixing the modified alumina and the transition metal precursor, drying and calcining to obtain a modified alumina-metal composite carrier; S3. Mix the dispersion stabilizer and the noble metal precursor to obtain an impregnation solution, impregnate the impregnation solution onto the modified alumina-metal composite carrier, dry and calcine to obtain a bimetallic, bidispersion stabilizer catalyst.

7. The method for preparing a bimetallic, bidisperse stabilizer catalyst according to claim 6, characterized in that: The mixing temperature in step S1 is 10 to 60°C and the mixing time is 1 to 4 hours. The inlet air temperature for spray drying is 250-400°C.

8. The method for preparing a bimetallic, bidisperse stabilizer catalyst according to claim 6, characterized in that: The temperature of the mixed molding in step S2 is 10 to 60°C. The drying temperature is 80-150°C and the drying time is 2-6 hours. The calcination temperature is 500-700°C and the calcination time is 2-6 hours.

9. The method for preparing a bimetallic, bidisperse stabilizer catalyst according to claim 6, characterized in that: The mixing temperature in step S3 is 40 to 80°C and the mixing time is 0.5 to 2 hours. The impregnation adopts equal volume impregnation, the impregnation temperature is 10-60℃, and the time is 0.5-2h. The drying temperature is 80-150°C and the drying time is 2-6 hours. The calcination temperature is 400-600°C and the calcination time is 2-6 hours.

10. Use of a bimetallic, bidisperse stabilizer catalyst as claimed in any one of claims 1 to 5, characterized in that: The catalyst is used for catalytic oxidation of reducing gas or volatile organic matter.

Citation Information

Patent Citations

  • Monolithic catalyst for coal mine low-concentration ventilation air methane (VAM) combustion and preparation method thereof

    CN102500393A

  • High-specific-surface-area perovskite catalyst LaCo0.9Mg0.1O3 and preparation method thereof

    CN103372447A

  • Flame-retarding polyvinyl chloride plastic particles and preparation method thereof

    CN109306136A

  • Carbon monoxide catalytic combustion catalyst, preparation method thereof and application of catalyst

    CN109569678A